Emas dan Tanah: Kasus Penguasaan Sumber-sumber Ekonomi di Sumatera dan Jawa Pada Abad VII-X Masehi (Kajian Prasasti-prasasti Masa Sriwijaya dan Mataram Kuna) - Nurhadi Rangkuti (Balai Arkeologi Yogyakarta, 1994)
Inscriptions are sources of past history written on stone or metal. Most of these inscriptions were issued by order of kings or rulers, generally containing the number of years, lists of high royal officials, construction of holy buildings, establishment of perdikan (sima), religions, curses, court decisions, social organizations and religious organizations. As the ruling medium, inscriptions were used to announce the regulations, powers and decisions of the rulers relating to the political-economic interests of the rulers at that time. The subject matter in this paper is, to what extent the inscriptions as the media for the rulers convey and imply the policies of the rulers in political-economic interests at that time? Are there transparent differences in the strategy of control and regulation of economic resources, of the two civilizations that have different economic resources? From the comparison of the contents of the Srivijaya era inscriptions (VII century AD) and Old Mataram inscriptions (IX-X century AD), it appears that there are differences in the way of controlling the economic resources of the two kingdoms.